Anti-inflammatory and analgesic activities of methanol extracts of stem bark of Anthocleista djalonensis in wistar rats - Olusayo Aderonke Shorinwa, Adaora Obiageli Enemuoh, Fidelia Ijeoma Uche (Journal of Applied Pharmaceutical Science, 2015)
This study was carried out to evaluate the anti-inflammatory and analgesic activities of the stem bark extract in albino rats. Evaluation of the anti-inflammatory activity was done using fresh egg albumin induced rat paw edema with a plethysmometer, while the analgesic effect was determined using the analgesymeter mechanically induced pain. The methanolic extract of the stem bark of Anthocleista djalonensis was evaluated at 100mg/kg, 200mg/kg, and 400mg/kg through the oral route. Indomethacin (10mg/kg) was used as standard reference anti-inflammatory and analgesic drug. Preliminary phytochemical screening showed the presence of tannins, flavonoids, saponins and deoxysugars. The different doses of the extract significantly inhibited the egg albumin induced inflammation (P
Keywords: Anthocleista djalonensis , anti-inflammatory, analgesic, analgesymeter, plethysmometer.